Global crisis and natural resources: A developing country perspective. - van der Ploeg, F (NOW Publishers, 2009)
The global financial crisis has potentially many adverse effects on the developing world: falls in exports of goods and services to the OECD, dramatic falls in commodity prices and resource exports, and falls in remittances. Many of the poorer countries are heavily specialized and dependent on natural resources, often landlocked, ethnically polarized, and financially underdeveloped. They therefore suffer especially from the notorious volatility of natural resource prices. Volatile oil prices harm not only producers and consumers in the developing world, but also harm environmental quality if they hold back irreversible investments in costly energy-saving technology and hydrocarbon substitutes. In the aftermath of the crisis, political leaders should seek for a global deal whereby resource-rich developing countries are helped to cope with managing very volatile streams of resource revenues while cutting back pollution of the energy industries. The global crisis facing the world today is thus not only a financial crises, but also a fuel and commodity crisis. In addition, the world also faces a food, water, and climate change crisis, all of which undermine the ability to sustain prosperity and eradicate poverty in the developing world. Hence, the contours of a Global Green New Deal will be sketched.